World Economic Outlook, October 1992. (World Economic Outlook; World Economic Outlook, 1992)
This paper highlights that world economic activity showed signs of revival in the first half of 1992 as some major economies slowly began to emerge from the cyclical downturns of 1990-91. During the next 12 months, world growth is expected to continue to recover at a moderate pace. Following stagnation in 1991, world output is projected to expand by 1 percent in 1992 and by 3 percent in 1993, close to the average growth rate during the past two decades.